2014
DOI: 10.1104/pp.114.237511
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of Plasma Intrinsic Protein1 Aquaporin in Poplar Trees Is Detrimental to Recovery from Embolism    

Abstract: During their lifecycles, trees encounter multiple events of water stress that often result in embolism formation and temporal decreases in xylem transport capacity. The restoration of xylem transport capacity requires changes in cell metabolic activity and gene expression. Specifically, in poplar (Populus spp.), the formation of xylem embolisms leads to a clear up-regulation of plasma membrane protein1 (PIP1) aquaporin genes. To determine their role in poplar response to water stress, transgenic Populus tremul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
58
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 60 publications
8
58
0
Order By: Relevance
“…Specifically, plasma membrane intrinsic proteins (PIP) are often up-regulated before or during refilling. Secchi and Zwieniecki (2010) reported that Populus trichocarpa showed considerable up-regulation of the PIP1 subfamily of aquaporin water channels, and down-regulation of the same isoform was detrimental to recovery (Secchi and Zwieniecki 2014). In grapevines, two aquaporin genes were activated on stress or refilling, suggesting a specific role in xylem embolism refilling (Chitarra et al 2014).…”
Section: Recent Non-destructive Methodsmentioning
confidence: 99%
“…Specifically, plasma membrane intrinsic proteins (PIP) are often up-regulated before or during refilling. Secchi and Zwieniecki (2010) reported that Populus trichocarpa showed considerable up-regulation of the PIP1 subfamily of aquaporin water channels, and down-regulation of the same isoform was detrimental to recovery (Secchi and Zwieniecki 2014). In grapevines, two aquaporin genes were activated on stress or refilling, suggesting a specific role in xylem embolism refilling (Chitarra et al 2014).…”
Section: Recent Non-destructive Methodsmentioning
confidence: 99%
“…Research in this area has shown that PIP1 and PIP2 antisense lines do not exhibit reduced leaf and plant hydraulic conductivity under normal moisture conditions. However, the lack of functional PIPs results in the significantly slower recovery of plant hydraulic conductivity following exposure to drought (Martre et al, 2002;Secchi and Zwieniecki, 2014). Additional studies have described the Flexas et al, 2007) Data are given as means 6 SE (n, number of independent biological repetitions).…”
Section: Whole-plant Constitutive Silencing Of Pip Aqpsmentioning
confidence: 99%
“…Abscisic acid may accumulate in the roots during the drought period, reach after rehydration the leaves via the xylem, cause stomatal closure and improve as a consequence the water potential in various shoot parts facilitating the repair of embolism (Lovisolo et al, 2008). More recently Secchi and Zwieniecki (2014) reported a strong up-regulation of aquaporin gene expression when xylem embolism was formed. Furthermore, these authors concluded from experiments with transgenic poplar plants that the expression of aquaporin genes is important for the recovery from embolism.…”
Section: Solute Allocation Via the Xylemmentioning
confidence: 98%